ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI ISLAMIC SOCIAL REPORTING PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DALAM INDEKS SAHAM SYARIAH INDONESIA (ISSI) TAHUN 2011 – 2014 - FARICHA, NAILIL (Jurnal Akuntansi AKUNESA, 2015)
This study aimed to analyze factors - factors that affect disclosure ISR . The population in this study are company in Indonesia Sharia Stock Index ( ISSI ) in BEI . And the selection of the sample using purposive sampling method with the criteria of the mining sector companies that perform ISR and consistent disclosure in ISSI from year 2011 - 2014 as well as the use of currency. Sample obtained a number of 28 samples . The analytical method used is multiple regression method . Results from this study indicate that the company 's profitability and age did not significantly influence the ISR . Independent commissioners and firm size affect the disclosure of ISR .Keywords : Islamic Social Reporting , Indonesia Sharia Stock Index , Profitability , Independent Commissioner , Company Size , Age Company